"This is Jerusalem calling" : state radio in mandate Palestine - Stanton, Andrea L. (University of Texas Press, 2013)
This history of the long-overlooked Palestine Broadcasting Service (1936-1948) examines the role of government-sponsored radio in shaping Arab political and social life in the wake of British colonialism.